Role of the Sunda Strait in Water Mass Exchange and Circulation between the Java Sea and the Indian Ocean: a CROCO Model Experiment - Rahmawitri, Herwi; Atmadipoera, Agus Saleh; Hamzah, Faisal; Xu, Tengfei (POSITRON, 2026)
The Sunda Strait is the only shallow passage connecting the Sunda Shelf seas (including the Java Sea) to the eastern Indian Ocean, and it strongly influences near-surface circulation and the South Java–Sumatra upwelling system. Using a high-resolution three-dimensional CROCO configuration, we conduct paired numerical experiments with the strait open (control) and artificially closed to quantify its role in regional water-mass exchange and hydrographic variability. The control simulation indicates a seasonal reversal of exchange, with an intrusion of Indian Ocean water into the Java Sea during the northwest monsoon (DJF), contrasting with southward export during the southeast monsoon (JJA). The meridional volume transport varies between −0.47 Sv (southward) and 0.42 Sv (northward), with a mean of -0.13 ± 0.17 Sv (1 Sv = 10⁶ m³ s⁻¹). The closure (OFF-strait) experiment reveals the Sunda Strait acts as a crucial gateway that allows warmer and fresher Java Sea water to enter the Indian Ocean. When the strait is closed, this export is blocked, leading to higher sea surface height and stronger surface circulation on the Java Sea side, while sea surface temperature decreases on the Indian Ocean side—especially during JJA—consistent with enhanced upwelling. Conversely, the closure prevents salty and colder Indian Ocean water from penetrating into the Java Sea. Overall, the strait modulates both the intensity of South Java–Sumatra upwelling and the strength of surface circulation. These results improve understanding of Sunda Strait dynamics and provide a physical basis for assessing implications for marine productivity, fisheries, and climate-driven variability.